Application of Fuzzy Methods In Assessment of Educational Performance In Rectorate of Surabaya State University - Rahmad Bagus Pambudi; Widya Timur Panca Retno Ningsih; Andyka Bangun Wicaksono; Febry Irsiyanto Wahyu Utomo (CV Putra Publisher, 2023)
The aim of this research is to analyze employee performance assessments at the Rectorate of Surabaya State University. This research method uses qualitative with literature review. Data sources are studies of relevant journals and books. Data analysis using content analysis. The results of the research state that by calculating the criteria weights using the fuzzy AHP method, it is hoped that the assessment results will be more objective and accurate, which will then provide a picture of the state of the performance of educational staff which can actually be a reference in developing educational staff which will later support performance at PTNBH State University of Surabaya, output This research is in the form of an international journal.